2008
DOI: 10.1016/j.jhazmat.2008.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of titanium dioxide photocatalyst loaded onto activated carbon support using chemical vapor deposition: A review paper

Abstract: Various methods to prepare and characterize TiO(2) photocatalyst loaded onto activated carbon (AC) support have been developed over the last decade. This photocatalyst has been used in a variety of investigations, i.e. from water decontamination to direct pollutant degradation in aqueous and gas phase systems using UV irradiation and lately with the assistance of ultrasonic sound waves. Chemical vapor deposition (CVD) method is one of the most promising and well-researched methods for deposition of catalysts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
173
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 409 publications
(194 citation statements)
references
References 102 publications
0
173
0
4
Order By: Relevance
“…TiO 2 has been developed and used as a photocatalyst for indoor and outdoor air purification and to purify water contaminated with low concentrations of toxic pollutants. 150) …”
Section: Bake-out Methodsmentioning
confidence: 99%
“…TiO 2 has been developed and used as a photocatalyst for indoor and outdoor air purification and to purify water contaminated with low concentrations of toxic pollutants. 150) …”
Section: Bake-out Methodsmentioning
confidence: 99%
“…The UV lamp used in this research showed a strong intensity and the produced high energy photons have an important role for the VOC degradation (Shen and Ku, 1999). The authors reported that TiO2 loaded on AC activated by UV irradiation can act as electron carriers to stop recombination of electron-hole species, which would cause greater oxidation of o-xylene in the air stream (Puma et al, 2008). Davide Barreca et al (Barreca et al, 2009) proposed that AC loaded with a photocatalyst (such as TiO2 and ZnO) has the potency to decompose the intermediate products in situ which will enhance the removal efficiency of the photocatalyst.…”
Section: Influence Of Initial O-xylene Concentrationmentioning
confidence: 96%
“…Moreover, GAC can be used as catalyst support without a considerable decreeing of its BET surface and pore volume (El-Sheikh et al, 2004). Furthermore, it is reported that the pores of GAC are not blocked by the agglomeration of photocatalyst particles and there is a proportion between the pore volume reduction of GAC and its amount in the catalyst (Puma et al, 2008). Thus, it will be possible to take advantage of both adsorption and catalytic degradation processes by impregnating GAC with an efficient catalyst agent.…”
Section: Introductionmentioning
confidence: 99%
“…Using activated carbon as a support will also enable secondary degradation of intermediates to take place in situ, further enhancing the effectiveness of the photocatalyst. Moreover, using AC as a support allows for fast and easy photocatalyst recovery and provides ample room for catalyst regeneration using various techniques [11][12][13][14][15][16]18 . This is because the supported photocatalyst can be made into a granular form, providing an easy filtering option for recovery from the slurry 11 .…”
mentioning
confidence: 99%